ANÁLISIS DEL LIDERAZGO FEMENINO Y PODER ACADÉMICO EN EL CONTEXTO UNIVERSITARIO ESPAÑOL - Maria Pilar Caceres Reche; Antonio Sachicola; Maria Angustias Hinojo Lucena (European Scientific Journal, ESJ, 2015)
Although the integration of women in public life has been increasing in recent years still show difficulties in accessing senior or academic power positions in various fields, such as education. In this paper, this situation is analyzed from the conception of gender; as well as external and internal barriers to progress your career; questioning the existence of a possible female leadership in the low representation in positions of power and its link to a transformational style that must be developed from the organizational culture of schools itself, strengthening the balance in intergender relationship.